Analysis Of Consideration Of The Judge's Decision The Process Of Management And Settlement Of The Debtor's Property After The Bankruptcy Of The Debtor In Bankruptcy (Case Study No. 1/Pdt.Sus-Renvoi Prosedur/2022/PN.Niaga.Mdn) - Ariffani, Ariffani; Sahputra, Rilawadi; Azmi, Syaiful (International Asia Of Law and Money Laundering (IAML), 2023)
Research known bankruptcy property management process done after being decided by a court judge and seized the debtor's property bankruptcy by the curator, in this management curator will call the creditors to match the bill of receivables by holding a meeting verification, peace meetings and other meetings while on settlement if there is no peace agreement then the curator will sell and divide the assets that have been collected is reduced by bankruptcy costs and the rest will be shared with creditors, while that if the bankruptcy estate is not enough then creditors can take the effort law through the procedure renvoi, while the curator will still perform their duties to perform the division in accordance with pari passu principle pro rata parte, while in the judge's decision on level of the Commercial Court, Cassation and judicial review has been reflect justice and balance for the parties because in the judge's decision still considers the portion of the creditor's position preferred greater than the settlement of bankruptcy assets later the rest is distributed to other creditors fairly.